PENERAPAN MODEL PROBLEM-BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN ANALISIS SISWA PADA PEMBELAJARAN IPAS MATERI SUMBER ENERGI DI SEKITAR KITA DI KELAS III SDI OEPURA 2 KUPANG - Maria Vianey Moto Ose Tukan; Koro, Maxsel; Antonius Suban Hali (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Thesis by Maria Vianey Moto Ose Tukan NIM 2201140028 entitled “Implementation of the Problem Based Learning Model to Improve Students' Analytical Skills in IPS Learning about Energy Sources Around Us in Grade III at SDI Oepura 2, Kupang City.” The research problem formulation is: How is the implementation of the Problem Based Learning model in IPS learning about energy sources around us to improve the analytical skills of Grade III students at UPTD SDI Oepura 2? This research aims to improve students' analytical skills in understanding the material on energy sources around us through the implementation of the Problem Based Learning model. This type of research is Classroom Action Research with the following stages: planning, implementation, observation, and reflection. The subjects of this study were third-grade students, numbering 28 people, consisting of 15 boys and 13 girls. Data collection techniques were conducted through observation and documentation of the learning process as well as essay tests designed to measure three dimensions of analytical skills, namely differentiating, organizing, and attributing. The results of the study showed a consistent improvement in both the learning process and outcomes: the class average increased from 58.71 (pre-cycle) to 68.82 (Cycle I) and 85.60 (Cycle II), while classical completeness increased from 32% to 61% and then to 89%. These findings demonstrate the effectiveness of PBL in promoting meaningful learning engagement and strengthening the analytical skills of elementary school students through authentic problem-solving, collaboration, and targeted scaffolding.